NURSING EXERCISE IN PATIENTS ADMITTED BY RECENTLY DECOMPENSATED HEART FAILURE - THE ERIC PROGRAM - Bruno Delgado; Ivo Lopes; Eugénia Mendes; Bárbara Gomes; André Novo; Leonel Preto (Associação Portuguesa dos Enfermeiros de Reabilitação, 2018)
Background: Heart failure (HF) promomtes limitations on the activities of daily living and consequent loss of functional and instrumental autonomy. It represents one of the most concerning health problems due to its significant economic impact. Objective: To identify the impact of a physical exercise program on patients with HF in compensatory phase in hospital context. Methods: A retrospective exploratory study was carried out in which twenty patients who performed a minimum of 3 sessions of the ERIC program participated. Vital signs, ECG monitoring and subjective effort perception (PSE) were assessed before and after each training session, as well as LCADL scale and exercise parameters (number of laps in the pedal, number of meters walked in the hall and number of steps). The study presented took place over a period of 3 months. Results: Patients (mean age of 64 years) had a positive variation in the performance parameters of the exercise, a negative variation in LCADL scale (29.9 to 20.9) and SPE after exercise (4.85 to 3.82), which means that they improve their functional capacity throughout the program. None of them presented adverse events or trained outside the safety heart rate interval (mean value of 11.2 bpm to 12.9bpm). Conclusions: The ERIC program demonstrates safety and improvement of the Functional Capacity of the patient, based on the statistical analysis of this sample. These results allow us to infer that exercise can be an effective resource for the adjuvant treatment of patients admitted with decompensated heart failure. However, further studies with larger samples and a randomized design are needed.